Тарас Шевченко в критичній рецепції М. Плевака - Роспопа, Тетяна; Rospopa, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано публіцистичні та літературознавчі статті праці М. Плевако, присвячені творчості Т. Шевченка, виокремлено основні питання, що входили до сфери його дослідницьких інтересів у цій галузі. М. Плевако протягом 20 років XX століття розглядав постать Тараса Шевченка як титана української літератури, що не тільки зробив потужний внесок у літературу, а й став світочем українського духу. Представлені праці М. Плевака повнюють прогалини у бібліографуванні матеріалів про життя і творчість Т. Шевченка. The article deals with the journalistic and literary articlesd in M. Plevako work, devoted to the works of Taras Shevchenko, highlights the main issues that were part of the scope of the author's research interests in this area. M. Plevako over the 20 years of the XXth century has been denoting the figure of Taras Shevchenko as the titanium Ukrainian who not only made a contribution to the literature, but also became light of Ukrainian spirit. The presented works of M. Plevako were introduced not only to the scientific field but also fill gaps in arranging materials about the life and works of Taras Shevchenko. Shevchenkoznavchyy discourse of that time is represented by the scholars, who are different in many ways by general scientific approach and ideological foundation. These are such scholars as M. Sumtsov, D. Bahaliy, I. Aizenshtok, V. Koriak, Mashkin A., M. Plevako, M. Sulima, A. Sinyavsky, Alexander Beletsky, I. Pilhuk, I. Balak, S.Kryzhanivsky, S. Shakhovskyy and others. Understanding of the need of scientific and theoretical outline of shevchenkoznavstvo as a separate research direction raised interests of specialists, primarily literary critics and linguists to the issues, relating to the object, subject and study objectives of Shevchenko's artistic heritage, study methodological principles and denning research direction of specific searches. M. Plevako's works about Shevchenko demand to pass from their reading for the first time to the objective assessment and active entry to the scientific field.
Taras Shevchenko at the Critical Reception of M. Plevako
Keywords: шевченкознавство; українське літературознавство; Shevchenko studies; Ukrainian literature